2020
DOI: 10.1186/s40795-020-00388-x
|View full text |Cite
|
Sign up to set email alerts
|

Food habits in pregnancy and its association with gestational diabetes mellitus: results from a prospective cohort study in public hospitals of urban India

Abstract: Background Few studies have explored the relationship between food habits and the risk of gestational diabetes mellitus (GDM) in women from India. We aimed to investigate the associations of food habits and the risk of GDM. Methods As part of the MAASTHI prospective cohort study in urban Bengaluru, India, pregnant women between 18 and 45 years, less than 36 weeks of gestation were included. During baseline, the participant’s age, education, physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The present study found that the highest tertile of red meat protein (≥2.94 g protein per day or equivalent to roughly 12 g of cooked red meat per day) in the second trimester was significantly associated with the risk of developing GDM. The previous studies have shown inconsistent results, with the two studies suggesting significant associations (15,43) and one study demonstrated a non-significant association (8). However, direct comparisons between the studies could not be made because different measurements for meat intake were used.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present study found that the highest tertile of red meat protein (≥2.94 g protein per day or equivalent to roughly 12 g of cooked red meat per day) in the second trimester was significantly associated with the risk of developing GDM. The previous studies have shown inconsistent results, with the two studies suggesting significant associations (15,43) and one study demonstrated a non-significant association (8). However, direct comparisons between the studies could not be made because different measurements for meat intake were used.…”
Section: Discussionmentioning
confidence: 96%
“…A cohort study in China showed that the women with the highest meat intake (pork, beef, chicken, or lamb) had a higher risk for GDM than those in the lowest meat intake tertile (15). Similarly, a prospective study on the association between the food habits and the GDM risk in India showed that eating red meat more than three times per week was significantly associated with the GDM risk after adjusted for the covariates (43). In contrast, a cohort study in Singapore (Growing Up in Singapore Toward healthy Outcomes-GUSTO study) showed that higher protein from red meat was not significantly associated with a higher risk of GDM (8).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown, in a recent study, that GDM pregnant women show special food preferences such as lower intake of vegetables, fish, poultry, and fish paste. This correlates with microbiome diversity [ 73 ]. In this context, the use of probiotics as a novel therapeutic strategy appears to be appealing in the prevention of type 2 diabetes mellitus in post-GDM women.…”
Section: Human Microbiome and Microbiota Dysbiosis In Human Diseasesmentioning
confidence: 99%
“…However, from our point of view, the guidelines did not include all the important aspects of a healthy diet for all women before and during pregnancy and during lactation. 11 Not all of the suggestions proposed by national health-related groups were included in the final DGA document, and thus, there is ample room for differences in opinion regarding some aspects of nutrition in pregnancy.…”
Section: Concerns Regarding Red Meat Consumption During Pregnancy: a ...mentioning
confidence: 99%